The Effects of Entrepreneurial Marketing on Business Performance through Competitive Advantage and Product Innovation - Fatlur Rhozi; Ernani Hadiyati; Umi Muawanah (Research Horizon, 2026)
MSMEs play a crucial role in Indonesia’s economy, with batik representing a culturally and economically significant sector that contributes to growth, employment, and regional industrial competitiveness. The objective of this study is to analyze the effect of entrepreneurial marketing on business performance, competitive advantage, and product innovation, as well as to examine the mediating roles of competitive advantage and product innovation. This research employs a quantitative approach using the SEM-PLS method. Data were collected through questionnaires. The results indicate that entrepreneurial marketing has a positive and significant effect on business performance, competitive advantage, and product innovation. However, both product innovation and competitive advantage do not have a significant effect on business performance. Furthermore, competitive advantage and product innovation are not proven to mediate the relationship between entrepreneurial marketing and business performance. These findings highlight that entrepreneurial marketing significantly improves MSME performance through direct effects, while its indirect effects via competitive advantage and innovation are not supported. This study suggests that innovation and competitive positioning alone are insufficient without strong market alignment, emphasizing the importance of customer-oriented and adaptive entrepreneurial marketing for sustainable growth.